Process-Structure-Properties in Polymer Additive Manufacturing II - Sing, Swee Leong; Yeong, Wai Yee (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Additive manufacturing (AM) methods have grown and evolved rapidly in recent years. AM for polymers is particularly exciting and has great potential in transformative and translational research in many fields, such as biomedicine, aerospace, and even electronics. The current methods for polymer AM include material extrusion, material jetting, vat polymerization, and powder bed fusion. In this Special Issue, state-of-the-art reviews and current research results, which focus on the process-structure-properties relationships in polymer additive manufacturing, are reported. These include, but are not limited to, assessing the effect of process parameters, post-processing, and characterization techniques.